Peningkatan Kemandirian Desa Melalui Pembangunan Instalasi Perpipaan Air Bersih dari Sumber Mata Air ke Rumah Penduduk - Sukamta Sukamta; Sudarja Sudarja; Budi Nurrahman; Berli Paripurna Kamiel; Sudarisman Sudarisman (Universitas Muhammadiyah Yogyakarta, 2019)
Community empowerment program to make a village independent is very important. Village independence could be seen from various aspects, and one of which is the aspect of independence in the provision of clean water. Clean water supply activities in Balong Hamlet, Donoharjo Village, Ngaglik Sub- District, Sleman Regency are community empowerment activities in order to make Balong Hamlet independent on the aspect of the ability to provide clean water. This activity began with a survey and data collection of local residents’ water needs, followed by calculation of clean water requirements, design of clean water supply and distribution systems, implementation of piping installation, commissioning tests, economic analysis, and its contribution in making the village independent of clean water. This activity produces a piping system for clean water from the spring to the houses of Balong hamlets with a population of approximately 203 households. On average, each household needs 600 liters/day so it requires 121.8 m3 /day or 3654 m3 /month. The price of standard clean water for the Drinking Water Company (PAM) is Rp1,960.00/m3 , so the hamlet has saved Rp7,161,840.00/month or Rp85,942,080.00/year. Thus, this activity has made Balong Hamlet contribute significantly to the independence of Donoharjo Village.